Measurement of the pseudoscalar decay constant f(Ds) using charm-tagged events in e(+)e(-) collisions at root s=10.58.GeV - Aubert, B; Barate, R; Bona, M; Boutigny, D; Couderc, F; Karyotakis, Y; Lees, J; Poireau, V; Tisserand, V; Zghiche, A; Grauges, E; Palano, A; et al. (2007)
Using 230.2fb-1 of e+e- annihilation data collected with the BABAR detector at and near the peak of the Υ(4S) resonance, 489±55 events containing the pure leptonic decay Ds+→μ+νμ have been isolated in charm-tagged events. The ratio of partial widths Γ(Ds+→μ+νμ) /Γ(Ds+→ π+) is measured to be 0.143±0.018±0.006 allowing a determination of the pseudoscalar decay constant fDs= (283±17±7±14)MeV. The errors are statistical, systematic, and from the Ds+→ π+ branching ratio, respectively. © 2007 The American Physical Society.